2013
DOI: 10.1038/nature12337
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis regulatory network and hypoxia

Abstract: We have taken the first steps towards a complete reconstruction of the Mycobacterium tuberculosis regulatory network based on ChIP-Seq and combined this reconstruction with system-wide profiling of messenger RNAs, proteins, metabolites and lipids during hypoxia and re-aeration. Adaptations to hypoxia are thought to have a prominent role in M. tuberculosis pathogenesis. Using ChIP-Seq combined with expression data from the induction of the same factors, we have reconstructed a draft regulatory network based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
569
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(595 citation statements)
references
References 45 publications
26
569
0
Order By: Relevance
“…Again, the transition from a metabolically active state to a dormant state is dysregulated within Mtb: ⌬Rv2745c. Of particular note, fas and accD4, which are involved in lipid metabolism, are shown to be down-regulated upon hypoxic conditions, which we also found within our study (7).…”
Section: Volume 290 • Number 4 • January 23 2015supporting
confidence: 73%
“…Again, the transition from a metabolically active state to a dormant state is dysregulated within Mtb: ⌬Rv2745c. Of particular note, fas and accD4, which are involved in lipid metabolism, are shown to be down-regulated upon hypoxic conditions, which we also found within our study (7).…”
Section: Volume 290 • Number 4 • January 23 2015supporting
confidence: 73%
“…Previous ChIP-Seq and transcriptome analysis of Mycobacterium tuberculosis have clearly demonstrated that novel and functionally relevant binding sites can be identified with high frequency in the relatively large number of smaller ChIP-Seq peaks (Galagan et al, 2013;Gao et al, 2012). Given this precedent, the numerous new candidate targets (particularly those containing instances of MC-Motif 1 and MC-Motif 2; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Galagan et al carried out proteome profiling of dormant and re-aerated MTB using a defined hypoxia model, and identified a total of approximately one thousand proteins (26). The process of reactivation of MTB from dormancy is a critical step in the development of active TB.…”
mentioning
confidence: 99%